2020
DOI: 10.1002/adma.202000608
|View full text |Cite
|
Sign up to set email alerts
|

The True Amphipathic Nature of Graphene Flakes: A Versatile 2D Stabilizer

Abstract: The fundamental colloidal properties of pristine graphene flakes remain incompletely understood, with conflicting reports about their chemical character, hindering potential applications that could exploit the extraordinary electronic, thermal, and mechanical properties of graphene. Here, the true amphipathic nature of pristine graphene flakes is demonstrated through wet‐chemistry testing, optical microscopy, electron microscopy, and density functional theory, molecular dynamics, and Monte Carlo calculations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…We first evaluated the effects of graphene flakes on steady-state actin polymerization using TIRF microscopy imaging. We chose pristine graphene flakes rather than graphene oxide flakes or its derivatives since pure graphene flakes have well-defined hydrophilic and hydrophobic regions, demonstrated by a recent study [ 35 ]. We polymerized actin filaments (18–20% Alexa-labeled) in the absence (control) or presence of graphene flakes (0.5–20 μg/mL), and then measured the steady-state actin filament lengths in the presence of graphene flakes (0.5–20 μg/mL) ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We first evaluated the effects of graphene flakes on steady-state actin polymerization using TIRF microscopy imaging. We chose pristine graphene flakes rather than graphene oxide flakes or its derivatives since pure graphene flakes have well-defined hydrophilic and hydrophobic regions, demonstrated by a recent study [ 35 ]. We polymerized actin filaments (18–20% Alexa-labeled) in the absence (control) or presence of graphene flakes (0.5–20 μg/mL), and then measured the steady-state actin filament lengths in the presence of graphene flakes (0.5–20 μg/mL) ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…[65,66] Graphene particles stabilize oil droplets by attracting water at the corners on the other hand repelling the water on the surface. [66] When microcapsules were coated on PET fabrics, it was observed that the microcapsules remained between warp and weft threads. However, a coating was obtained in which the microcapsules were homogeneously distributed over the fabric surface.…”
Section: Size and Morphology Analysismentioning
confidence: 99%
“…The graphene particles in the emulsion act as a surfactant, causing the PCM droplets to decrease in diameter. [65,66] Graphene particles stabilize oil droplets by attracting water at the corners on the other hand repelling the water on the surface. [66] When microcapsules were coated on PET fabrics, it was observed that the microcapsules remained between warp and weft threads.…”
Section: Size and Morphology Analysismentioning
confidence: 99%
“…The electrical conductivity of the graphene structure is partly regained, and rGO can be dispersed in various solvents [15], including water, forming stable suspensions that can be used for deposition on various surfaces. Additionally, due to the presence of hydrophobic (basal planes) and hydrophilic domains, rGO is amphiphilic and can be used for foam or Pickering emulsions stabilization [16,17]. Furthermore, the functional groups remaining after the reduction process facilitate covalent modification by attachment of various functional groups, ligands, etc.…”
Section: Introductionmentioning
confidence: 99%